The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijerph192316303
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Mechanism of the Impact of Green Finance and Digital Economy on China’s Green Total Factor Productivity

Abstract: In the context of the “double cycle,” promoting the development of a green economy is an important goal for China’s high-quality economic development in the digital age. This paper uses data from 30 provinces (municipalities and autonomous regions) in China during the 2006–2019 period using the Compiled Green Finance Index (GF) and Digital Economy Index (DE). The interrelationship between green finance, digital economy and green total factor productivity (GTFP) is empirically tested by conducting multiple regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…Thirdly, the promotion effect of the level of development of the digital economy on ecological protection and green development. Based on the urban panel data of 280 prefecture-level cities in China from 2011-2019, Guo and Ma (2022) used component analysis and SBM-Malmquist method to measure the level of development of the digital economy and green total factor productivity in China's major cities, and conducted an empirical analyses on it. The results show that the digital economy has a significant driving effect on urban green total factor productivity, that is, the digital economy can indirectly promote urban green total factor productivity by enhancing green innovation, and industrial structure upgrading (Guo and Ma, 2022).…”
Section: Journal Of Internetmentioning
confidence: 99%
“…Thirdly, the promotion effect of the level of development of the digital economy on ecological protection and green development. Based on the urban panel data of 280 prefecture-level cities in China from 2011-2019, Guo and Ma (2022) used component analysis and SBM-Malmquist method to measure the level of development of the digital economy and green total factor productivity in China's major cities, and conducted an empirical analyses on it. The results show that the digital economy has a significant driving effect on urban green total factor productivity, that is, the digital economy can indirectly promote urban green total factor productivity by enhancing green innovation, and industrial structure upgrading (Guo and Ma, 2022).…”
Section: Journal Of Internetmentioning
confidence: 99%
“…This leads to a pattern of latecomer disadvantage in China's regional growth 8 . Some in their empirical study indicate that the central and western regions, due to a lack of resource endowments and inherent deficiencies in industrial foundations and innovation capabilities, not only find it difficult to enhance TFP through the digital economy, but may even experience a suppression in productivity 9 . Others suggest that the development of the digital economy accentuates the siphoning effect in the southeastern coastal regions, thereby widening the TFP gap on either side of China's Hu Huanyong Line in the short term 10 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhao et al (2020) found that the digital economy can enhance entrepreneurial activity and promote high-quality economic development using empirical research on the panel data of 222 cities above the prefecture level in China. In addition, several studies have analyzed the impact of DT on trade in services (Zhou L. et al, 2023), total factor energy efficiency (Fu et al, 2023;Huang et al, 2023), knowledge innovation (Orlando et al, 2020;Wang and Li, 2023), economic growth (Qu et al, 2017), air pollution , and green total factor productivity (Guo et al, 2022;Zhao et al, 2022).…”
Section: The Economic Effects Of Digital Technologymentioning
confidence: 99%